Change in alcohol outlet density and alcohol-related harm to population health (CHALICE): a comprehensive record-linked database study in Wales - David Fone; Jennifer Morgan; Richard Fry; Sarah Rodgers; Scott Orford; Daniel Farewell; Frank Dunstan; James White; Vas Sivarajasingam; Laszlo Trefan; Iain Brennan; Shin Lee; et al. (NIHR Journals Library, 2016)
Background: Excess alcohol consumption has serious adverse effects on health and results in violence-related harm. Objective: This study investigated the impact of change in community alcohol availability on alcohol consumption and alcohol-related harms to health, assessing the effect of population migration and small-area deprivation. Design: A natural experiment of change in alcohol outlet density between 2006 and 2011 measured at census Lower Layer Super Output Area level using observational record-linked data. Setting: Wales, UK; population of 2.5 million aged ≥ 16 years. Outcome measures: Alcohol consumption, alcohol-related hospital admissions, accident and emergency (A&E) department attendances from midnight to 06.00 and violent crime against the person. Data sources: Licensing Act 2003 [Great Britain. Licensing Act 2003. London: The Stationery Office; 2003. URL: www.legislation.gov.uk/ukpga/2003/17/contents (accessed 8 June 2015)] data on alcohol outlets held by the 22 local authorities in Wales, alcohol consumption data from annual Welsh Health Surveys 2008-12, hospital admission data 2006-11 from the Patient Episode Database for Wales (PEDW) and A&E attendance data 2009-11 were anonymously record linked to the Welsh Demographic Service age-sex register within the Secure Anonymised Information Linkage Databank. A final data source was recorded crime 2008-11 from the four police forces in Wales. Methods: Outlet density was estimated (1) as the number of outlets per capita for the 2006 static population and the per quarterly updated population to assess the impact of population migration and (2) using new methods of network analysis of distances between each household and alcohol outlets within 10 minutes of walking and driving. Alcohol availability was measured by three variables: (1) the previous quarterly value; (2) positive and negative change over the preceding five quarters; and (3) volatility, a measure of absolute quarterly changes during the preceding five quarters. Longitudinal statistical analysis used multilevel Poisson models of consumption and Geographically Weighted Regression (GWR) spatial models of binge drinking, Cox regression models of hospital admissions and A&E attendance and GWR models of violent crime against the person, each as a function of alcohol availability adjusting for confounding variables. The impact on health inequalities was investigated by stratifying models within quintiles of the Welsh Index of Multiple Deprivation. Results: The main finding was that change in walking outlet density was associated with alcohol-related harms: consumption, hospital admissions and violent crime against the person each tracked the quarterly changes in outlet density. Alcohol-related A&E attendances were not clinically coded and the association was less conclusive. In general, social deprivation was strongly associated with the outcome measures but did not substantially modify the associations between the outcomes and alcohol availability. We found no evidence for an important effect of population migration. Limitations: Limitations included the absence of any standardised methods of alcohol outlet data collation, processing and validation, and incomplete data on on-sales and off-sales. We were dependent on the quality of clinical coding and administrative records and could not identify alcohol-related attendances in the A&E data set. Conclusion: This complex interdisciplinary study found that important alcohol-related harms were associated with change in alcohol outlet density. Future work recommendations include defining a research standard for recording outlet data and classification of outlet type, the methodological development of residence-based density measures and a health economic analysis of model-predicted harms. Funding: The National Institute for Health Research Public Health Research programme. Additional technical and computing support was provided by the Farr Institute at Swansea University, made possible by the following grant:: Centre for the Improvement of Population Health through E-records Research (CIPHER) and Farr Institute capital enhancement. CIPHER and the Farr Institute are funded by Arthritis Research UK, the British Heart Foundation, Cancer Research UK, the Chief Scientist Office (Scottish Government Health Directorates), the Economic and Social Research Council, the Engineering and Physical Sciences Research Council, the Medical Research Council, the National Institute for Health Research, the National Institute for Social Care and Health Research (Welsh Government) and the Wellcome Trust (grant reference MR/K006525/1).